ENR-50 compatibilized natural rubber/recycled acrylonitrile-butadiene rubber blends - Hazwani Syaza Ahmad; Hanafi Ismail; Azura Abd Rashid (Universiti Kebangsaan Malaysia, 2015)
Epoxidized natural rubber (ENR-50) has been used as a compatibilizer for natural rubber-recycled acrylonitrile-butadiene rubber (NR/NBRr) blends, vulcanized by sulfur. NBR gloves have excellent resistance to punctures, tear and many types of chemicals, while NR has good physical and mechanical properties. Incorporation of ENR-50 into the rubber blends has improved processability, stiffness, resilience and excellent oil resistance. NR/NBRr blends were prepared by two-roll mill with five different compositions with the ENR-50 content fixed at 10 phr. Cure characteristics, mechanical properties and morphology (SEM) studies were performed to determine the compatibility of NR/NBRr blends in the presence of ENR-50. The cure characteristics showed that NR/NBRr blends with the presence of ENR-50 have lower scorch time (ts2) and cure time (t90) than NR/NBRr blends without ENR-50. However, the NR/NBRr blends with ENR-50 exhibited higher minimum torque (ML) and maximum torque (MH) which indicated difficult processability of the blends after compatibilization. Incorporation of ENR-50 into NR/NBRr blends improved all the tensile properties (tensile strength, tensile modulus and elongation at break) compared with NR/NBRr blends without ENR-50. The improvement in hardness upon compatibilization is due to an increase in crosslink density. Scanning electron microscopy (SEM images) of the fracture surfaces indicates that, with the addition of ENR-50 in NR/NBRr blends, better adhesion between NR and NBRr was obtained, thus improving the compatibility of NR/NBRr blends.